Asylrecht und Asylpolitik in der Europäischen Union: eine deutsch-ungarische Perspektive - Anderheiden, Michael; Brzózka, Helena; Hufeld, Ulrich; Kirste, Stephan (Schriftenreihe des Arbeitskreises Europäische Integration e.V, 2018)
The European Union’s policy on refugees and asylum is facing a historic challenge. The situation of worldwide migration has changed dramatically, necessitating the EU to enact well-coordinated common asylum legislation. However, the political desire for major reform in this respect seems to be lacking. The bilateral relations between Germany and Hungary have made it obvious that achieving consensus on this issue among the EU’s Member States is not yet possible and may even have to face setbacks. In May 2016, the Andrássy University in Budapest organised an academic symposium on the right of asylum and asylum policy. This volume features the updated written versions of articles presented at that symposium, which discuss the foundations of European migration policy from historical, philosophical and human rights perspectives, its requirements with regard to international law, the authoritativeness of European values, primary and secondary EU legislation and, finally, the Hungarian perspective on asylum law as a ‘means of isolation’.With contributions byMichael Anderheiden, Helena Brzózka, Oliver Diggelmann, Walter Frenz, Dóra Frey, Nina Hadorn, Caroline Hemler, Stephan Kirste, Peter-Christian Müller-Graff, Boldizsár Nagy, Pál Sonnevend